2004
DOI: 10.2527/2004.8272013x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carnichrome on the energy balance of gestating sows12

Abstract: Twelve multiparous sows with an average initial weight of 182 kg were used in a randomized complete block design to determine the effects of feeding Carnichrome (50 mg of carnitine and 200 microg of chromium picolinate per kilogram of feed, as fed) on energy and nitrogen utilization in early, mid-, and late gestation. All sows were fed a diet with or without Carnichrome for the preceding 28-d lactation, the weaning-to-estrus period, and for the duration of gestation. Daily feeding allowances over pregnancy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Decreased AHP is connected with a significantly decreased time that gestating sows spent on physical activity. Consistent with other studies ( Rijnen et al., 2003 ; Young et al., 2004 ), sows produced 0.24 kJ/kg BW 0.75 heat per minute of physical activity (sitting and standing) in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Decreased AHP is connected with a significantly decreased time that gestating sows spent on physical activity. Consistent with other studies ( Rijnen et al., 2003 ; Young et al., 2004 ), sows produced 0.24 kJ/kg BW 0.75 heat per minute of physical activity (sitting and standing) in this study.…”
Section: Discussionsupporting
confidence: 92%
“…(2003) reported sows spent 87.7% of their day resting and about 12.5% doing physical activity and eating. However, an inconsistent result was reported by Young et al. (2004) who found gestating sows fed one meal per day spent about 17% of their day sitting and standing.…”
Section: Discussionmentioning
confidence: 90%
“…It has been, moreover, found that l -carnitine increases body weight and backfat thickness in sows during gestation ( 34 ) . This finding prompted Young et al ( 75 ) to the hypothesis that carnitine improves energy utilisation in sows. These authors were able to demonstrate that Carnichrome, a combination of l -carnitine and chromium, improves the digestibility of energy and organic matter from the diet but has no influence on heat production.…”
Section: Hormonal and Metabolic Changes By L-carnitine Supplementatio...mentioning
confidence: 99%